1975
DOI: 10.1016/0022-4596(75)90315-1
|View full text |Cite
|
Sign up to set email alerts
|

Defects and the electronic properties of Y3Fe5O12

Abstract: The electrical and the optical absorption properties of yttrium iron garnet (YIG) are investigated. The stoichiometry is studied by means of lattice constant measurements and the defect mechanism is discussed. From high-temperature conductivity measurements at various oxygen pressures the band-gap energy is determined to be 2.85 eV. The influence of extrinsic impurities (Pb and Si) on the electrical conductivity and the optical absorption is investigated on thin &ns grown by liquid phase epitaxy. On the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 13 publications
(5 reference statements)
2
12
0
Order By: Relevance
“…Nevertheless, it has been shown that in some iron oxides, including LiFe 5 O 8 and GaFeO 3 , apparently forbidden crystal field d – d transitions may become allowed through antiferromagnetic spin coupling between next-nearest neighbor Fe atoms . According to literature reports, absorption bands at wavelengths below 413 nm can be ascribed to both oxygen-to-iron and oxygen-to-yttrium charge transfer (CT) as well as intervalence transitions between Fe 3+ ions on the tetrahedral and octahedral sites. The optical band gap at room temperature was found to lie in the range 2.6–2.9 eV and has been shown to arise due to excitation from O 2p valence band to Fe oct 3d conduction band. For this reason, YIG is referred to as a charge-transfer insulator. We estimate the band gap energy, E g , from the data for a direct transition as being (2.84 ± 0.05) eVthe lack of the characteristic shape of the plot α 1/2 versus photon energy argues against an indirect optical transition in the KLE-templated YIG thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been shown that in some iron oxides, including LiFe 5 O 8 and GaFeO 3 , apparently forbidden crystal field d – d transitions may become allowed through antiferromagnetic spin coupling between next-nearest neighbor Fe atoms . According to literature reports, absorption bands at wavelengths below 413 nm can be ascribed to both oxygen-to-iron and oxygen-to-yttrium charge transfer (CT) as well as intervalence transitions between Fe 3+ ions on the tetrahedral and octahedral sites. The optical band gap at room temperature was found to lie in the range 2.6–2.9 eV and has been shown to arise due to excitation from O 2p valence band to Fe oct 3d conduction band. For this reason, YIG is referred to as a charge-transfer insulator. We estimate the band gap energy, E g , from the data for a direct transition as being (2.84 ± 0.05) eVthe lack of the characteristic shape of the plot α 1/2 versus photon energy argues against an indirect optical transition in the KLE-templated YIG thin films.…”
Section: Resultsmentioning
confidence: 99%
“…An energy level diagram is sketched in Fig. 4, the ordering of the states follows Larsen and Metselaar [13]. The exchange interactions are Jad = -39.8 K, Jdd = -13.4 K, and Jaa = -3.8 K.…”
Section: Fe3 O4mentioning
confidence: 95%
“…( 1) O. denotes oxygen ions on a normal lattice site, V. are oxygen vacancies, e are electrons, O*(g) denotes gaseous oxygen molecules and the dots and dashes indicate positive and negative charges relative to the normal charge of the neutral lattice.…”
Section: O * Vo" + Me' + K 02(g)mentioning
confidence: 99%